PENILAIAN KEWAJARAN DAN PENGAMBILAN KEPUTUSAN INVESTASI SAHAM PT INDUSTRI JAMU DAN FARMASI SIDO MUNCUL Tbk - Dina Yeni Martia; Rika Wati; Mirasanti Wahyuni; Kenneth Pinandhito (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2020)
This study aims to define the rationality of stock prices and make the right investment decisions of PT Industri Jamu and Pharmaceuticals Sido Muncul Tbk shares (IDX stock code: SIDO) 2015-2019. This research employs the Free Cash Flow to Equity (FCFE) method. The results showed that the stocks of PT Industri Jamu dan Farmasi Sido Muncul Tbk were in an overvalued condition throughout the 2015 to 2019 period. Therefore, the right investment decision is to sell the shares of PT Industri Jamu and Pharmaceutical Sido Muncul Tbk if they already own these shares. Meanwhile, for potential investors interested in buying shares of PT Industri Jamu dan Pharmaceuticals Sido Muncul Tbk, they should adjust their investment strategy. The overvalued condition of SIDO's shares was accompanied by an increase in the stock market price. This situationfurnishes a positive signal that PT Industri Jamu and Pharmacy Sido Muncul Tbk has decent performance and virtuous long-term prospects. Hence, the shares of PT Industri Jamu and Pharmaceutical Sido Muncul Tbk are suitable for long-term investment.